Scutellarin Reduce the Homocysteine Level and Alleviate Liver Injury in Type 2 Diabetes Model - Wang, Yiyu; Fan, Xiaoming; Fan, Biao; Jiang, Kerong; Zhang, Haoxin; Kang, Feng; Su, Hui; Gu, Danshan; Li, Shude; Lin, Shaofang (Frontiers in Pharmacology, 2020)
Scutellarin (SCU) is an active ingredient extracted from Erigeron breviscapus (Vaniot) Hand.-Mazz. Its main physiological functions are anti-inflammatory and antioxidant. In this study, we established a STZ-induced model of type 2 diabetes (T2DM) and a homocysteine (Hcy)-induced apoptosis model of LO2 to investigate whether SCU can alleviate liver damage by regulating Hcy in type 2 diabetes. Biochemical analysis indicated that SCU could improve the lipid metabolism disorder and liver function in diabetic rats by downregulating the levels of triglycerides (TG), cholesterol (CHO), low-density lipoprotein (LDL), alanine transaminase (ALT) and aspartate transaminase (AST), and by upregulating the level of high-density lipoprotein (HDL). Interestingly, SCU also could down-regulate the levels of Hcy and insulin and enhance the ability of type 2 diabetic rats to regulate blood glucose. Mechanistically, our results indicated that SCU may control the level of Hcy through regulating the levels of β-Cystathionase (CBS), γ-Cystathionase (CSE) and 5,10-methylenetetrahydrofolate (MTHFR) in liver tissue, and up-regulate folic acid, VitB6 and VitB12 levels in serum. Furthermore, SCU inhibits apoptosis in the liver of T2DM rats and in cultured LO2 cells treated with Hcy. Together, our findings suggest that SCU may alleviate the liver injury thorough downregulating the level of Hcy in T2DM rats.